Spasticity Mechanisms – for the Clinician - Chakravarty, Ambar; Mukherjee, Angshuman (Frontiers in Neurology, 2010)
Spasticity, a classical clinical manifestation of an upper motor neuron lesion, has been traditionally and physiologically defined as a velocity dependent increase in muscle tone caused by the increased excitability of the muscle stretch reflex. Clinically spasticity manifests as an increased resistance offered by muscles to passive stretching (lengthening) and is often associated with other commonly observed phenomenon like clasp-knife phenomenon, increased tendon reflexes, clonus and flexor and extensor spasms. The key to the increased excitability of the muscle stretch reflex (muscle tone) is the abnormal activity of muscle spindles which have an intricate relation with the innervations of the extrafusal muscle fibers at the spinal level (feed-back and feed-forward circuits) which are under influence of the supraspinal pathways (inhibitory and facilitatory). The reflex hyperexcitability develops over variable period of time following the primary lesion (brain or spinal cord) and involves adaptation in spinal neuronal circuitries caudal to the lesion. It is highly likely that in humans, reduction of spinal inhibitory mechanisms (in particular that of disynaptic reciprocal inhibition) is involved. While simply speaking the increased muscle stretch reflex may be assumed to be due to an altered balance between the innervations of intra and extrafusal fibers in a muscle caused by loss of inhibitory supraspinal control, the delayed onset after lesion and the frequent reduction in reflex excitability over time, suggest plastic changes in the central nervous system following brain or spinal lesion. It seems highly likely that multiple mechanisms are operative in causation of human spasticity, many of which still remain to be fully elucidated.